PENGARUH PEMBERIAN REWARD TERHADAP HASIL BELAJAR SISWA PADA PELAJARAN MATEMATIKA KELAS IV SD DI SD NEGERI 101740 TANJUNG SELAMAT TAHUN PEMBELAJARAN 20182019 - SURBAKTI, AMELIA SEPTIANI (Unversitas Katolik Santo Thomas, 2019)
This study aims to determine the effect of giving rewards to student learning outcomes. This research was conducted at the Public Elementary School 101740 Tanjung Selamat in April 2019. The study sample consisted of 60 students. The method of this research is the Quasi experimental design method which in the design of this study there are two groups, namely, the experimental group and the control class. The instrument used to collect data is the multiple choice test. Hypothesis testing is done using the